2016
DOI: 10.5502/ijw.v6i3.529
|View full text |Cite
|
Sign up to set email alerts
|

Implicit theories of personal and social attributes: Fundamental mindsets for a science of wellbeing

Abstract: This paper argues for the fuller incorporation by wellbeing researchers of the implicit theories framework developed by social psychologist Carol Dweck and colleagues. This framework emphasises the role of entity ("fixed") and incremental ("growth") mindsets regarding personal and social attributes in the prediction and causation of psychological outcomes, including outcomes directly germane to feeling good and functioning well. Correlational, longitudinal, experimental, and meta-analytic findings are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
1
15
0
1
Order By: Relevance
“…Studies on mindset have generally argued that those with a growth mindset will perceive social and personal attributes as changeable, will have more positive emotional experiences and thus will have higher levels of thriving, flourishing and fulfillment [5,6]. However, more recent research has revealed that the positive results of growth mindset require certain contexts in which these positive outcomes could be possible [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mindset have generally argued that those with a growth mindset will perceive social and personal attributes as changeable, will have more positive emotional experiences and thus will have higher levels of thriving, flourishing and fulfillment [5,6]. However, more recent research has revealed that the positive results of growth mindset require certain contexts in which these positive outcomes could be possible [7].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have mostly focused on students' beliefs about intelligence (Blackwell et al 2007;Yeager and Dweck 2012). Students' beliefs that intelligence could be improved (growth mindset) predicted more positive outcomes than beliefs that it cannot be improved (fixed mindset) (Howell 2016;Komarraju and Nadler 2013).…”
mentioning
confidence: 99%
“…Theory of Self (Dweck, 1999; Dweck and Leggett, 1988) offers a cognition-affect-behaviour model suggesting individuals’ ‘implicit theories’ (deeply held beliefs) have important implications for their psychological functioning (Dweck et al, 1995). According to the model, children’s wellbeing and achievement are likely to be associated with the mindsets they adopt and learning goals they endorse (Duckworth et al, 2012; Howell, 2016; Yeager and Dweck, 2012). Children’s Theory of Self internally manifests as one of two types of mind-set: a fixed mindset (whereby, children believe they are made up of fixed traits), or a growth mindset (whereby, children believe that they are made up of changeable traits that they are capable of improving).…”
Section: Existing Evidence and Unexplored Landmentioning
confidence: 99%